Inside Cover: Resolving Sphingolipid Isomers Using Cryogenic Infrared Spectroscopy (Angew. Chem. Int. Ed. 32/2020). Issue 32 (22nd June 2020) - Kirschbaum, Carla; Saied, Essa M.; Greis, Kim; Mucha, Eike; Gewinner, Sandy; Schöllkopf, Wieland; Meijer, Gerard; von Helden, Gert; Poad, Berwyck L. J.; Blanksby, Stephen J.; Arenz, Christoph; Pagel, Kevin
Abstract : Ultracold, isolated lipids in the gas phase adopt specific conformations anchored by intramolecular interactions. In their Communication on page 13638, C. Arenz, K. Pagel, and co‐workers show that cryogenic infrared spectroscopy combined with quantum‐chemical calculations can reveal the three‐dimensional structure of lipids in the gas phase and allows double‐bond isomers to be distinguished.